THE EDUCATIONAL BACKGROUND OF IMAMS AND ITS CONTRIBUTION TO THEIR RECOGNITION AS RELIGIOUS LEADERS: THE CASE OF INDONESIAN MUSLIM COMMUNITY IN THE NETHERLANDS - Asep Muhammad Iqbal (Islam Realitas: Journal of Islamic and Social Studies, 2017)
The Netherlands is one of European countries whose population with Islamic background has been increasing significantly. Statistical data show that there are around one million Muslims in this country or around six per cent of total population of the Netherlands. Some Muslim communities in this country came from Southeast Asia including Indonesia. The number of Muslim population from Indonesia was estimated to be around 200,000 out of 400,000 Dutch population with Indonesian background. This certainly necessitates the involvement and role of religious leaders who are able to serve the need and interests of Muslim community with Indonesian backrgound in this country. One of the important issues needs attention is the educational background of these religious leaders. Therefore, this paper describes the following: what is the educational background of the imams and how this contributes to their recognition as religious leaders by Muslim community with Indonesian background in the Netherlands. It argues that the different patterns of educational background of imams among Indonesian Muslims in the Netherlands have significantly contributed to their recognition as respected religious leaders by their community. Dalam perkembangan kontemporer, Belanda merupakan salah satu negara Eropa di mana jumlah penduduknya yang berlatar belakang Islam mengalami peningkatan yang tinggi. Data statistik menunjukkan bahwa penduduk dengan latar belakang Islam berjumlah sekitar satu juta orang atau sekitar enam persen dari total populasi Belanda yang berjumlah sekitar tujuh belas juta orang. Penduduk Muslim ini sebagian berasal dari Asia Teggara termasuk Indonesia. Penduduk Muslim asal Indonesia diperkirakan berjumlah sekitar 200.000 orang dari sekitar 400.000 orang yang berlatar belakang Indonesia. Kenyataan ini menuntut keterlibatan dan peran pemimpin agama dalam melayani kebutuhan dan kepentingan umat Muslim asal Indonesia di negeri kincir angin ini. Salah satu hal yang menarik untuk dikaji dari para pemimpin agama ini adalah latar belakang pendidikan dan keilmuan mereka sehubungan dengan tugas-tugas keagamaan mereka. Karena itu, tulisan ini berupaya untuk mendeskripsikan pola latar-belakang pendidikan pemimpin keagamaan masyarakat Muslim asal Indonesia yang mana kemudian bisa dilihat kredibilitas dan kompetensi mereka dalam melayani umat. Artikel ini berargumen bahwa latar belakang pendidikan para imam asal Indonesia secara signifikan mempengaruhi pengakuan mereka sebagai pemimpin agama yang dihormati oleh komunitas Muslim asal Indonesia di Belanda.